COMPARATIVE STUDY ON THE DESTRUCTIVE BENDING MOMENTS OF SOME END CORNER JOINTS OF STRUCTURAL ELEMENTS OF SOLID BEECH WOOD WITH CROSS SECTION OF 50 X 25 MM - Kyuchukov, Borislav; Kyuchukov, Georgi; Jivkov, Vassil (Innovation in Woodworking Industry and Engineering design, 2013)
The paper shows the results of the studies on the strength characteristics of the end corner joints of the structural elements of solid beech wood with a cross section of 50 x 25 mm used in the construction of seating furniture. It has been found out that, on the basis of the values of the destructive bending moment, the non-dismountable end corner joints are arranged in the following descending order: halfopen mortise and tenon joint; blind stub mortise and tenon joint with dowel and cross dowel; blind stub mortise and tenon joint and dowel joints. It has been found out that, on the basis of the values of the destructive bending moment, the dismountable end corner joints are arranged in the following descending order: joints with two one-piece connectors “Confirmat” following by joint with two universal connectors with bolt and cross dowel. It is recommended to use the studies’ results in calculating the dimensions of seating furniture.